Investigation of Technical Stochastic Stability of Lateral Vibration of Mathematical Model of Rail Vehicle - Choromanski, W.; Kisilowski, J.; Łopata, H. (Engineering Transactions, 1985)
The authors present a method for investigating the technical stochastic stability of the mathematical model of a mechanical system With real input. The paper includes an algorithm which can be used in numerical applications. Sample results are given for a model of a four-axial luggage-car with coach 25 TN (Y25 Cs).